The objetual relations and the development of psiquism: a psychoanalytic conception - Ramírez, Natalia (2010)
The knowledge and research of the early human growing and development which have been constantly increasing in the last decade, motivates and encourages many researchers to analyze, investigate and take care of life itself at a very early age for optimizing the future individual development and colective as well of the entire society. It’s very important and neccesary for the child specially at early age to be immerse in society to ensure a very social and normal growing, yet more interesting and important is the crucial link and bondage that should be between child and mother specially at this early age, this issue have been worldwide studied and explored since war world II based on separations between mother and child and its devastaded consequences leaving the child with irreversible traumas for the rest of his life. The investigation of this current article tries to clarify and render an answer from diverse authors who have psychoanalytical points of view to those who have it otherwise which makes possible to understanding the human psychic and its eventual development.